A case study: assessing the impacts of open cut coal mining on the Maryvale Field (Yallourn) Open Cut and Morwell River Diversion through the use of finite element modelling - Narendranathan, S; Stipcevich, J; Rastogi, S (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
EnergyAustralia Pty Ltd–the current owners and operators of the Yallourn Open Cut coal mine–are planning to progress mining development into the Maryvale Field (MVF). Morwell River is located adjacent to the Western Batters of the MVF mine development. The upstream section is a meandering river channel with some realignments associated with mining in the adjacent Township Field (YTF), while the downstream section is an engineered Morwell River Diversion (MRD). A buffer zone between Western Batters and the Morwell River varies in width along Western Batters. The planned development at the MVF site poses some unique challenges in terms of slope stability and potential ground movement as mining activities progress. This paper presents a case study on the calibration and use of finite element models (FEMs) to assess the impacts of open cut mining activities on potential ground movement and slope stability of the MVF open cut mine and neighbouring natural Morwell River Channel and MRD.
Keywords: slope stability